Australian Law Postgraduate Network - Stephen Colbran; Belinda Tynan (Legal Education Review, 2006)
Radical legal education discourses are constructed as oppositional to orthodox legal education discourses such as doctrinalism and vocationalism, and emphasize the inadequacies of orthodox portrayals of law. Why are these radical discourses so often marginalized within the law school? In this paper I describe how this marginalization is a consequence of a range of external contingencies and the internal features of radical discourses, and suggest that marginalization is, perhaps, inevitable.